Analisis Kinerja Simpang Tak Bersinyal Pada Simpang Upah Kabupaten Aceh Tamiang - Gustina, Sri; Iqbal, Iqbal; Muammar, Rajib (Universitas Iskandar Muda, 2026)
The increase in the number of motorized vehicles in Indonesia has a direct impact on the performance of road networks and intersections, especially unsignalized intersections which have the potential to cause traffic congestion and accidents. This study aims to analyze the performance and determine the Level of Service (LOS) of the Upah Intersection, Karang Baru District, Aceh Tamiang Regency using the Indonesian Road Capacity Manual (MKJI) 1997 method. Field surveys were conducted over 3 days during morning, noon, and evening peak hours to collect traffic volume and intersection geometry data. The results show that the maximum traffic volume occurred on Monday evening, with values of 594 pcu/hour (North direction of the Medan–Banda Aceh Sumatra Cross Road), 794 pcu/hour (South direction of the Medan–Banda Aceh Sumatra Cross Road), and 544 pcu/hour (West direction of the Upah Market Road). The intersection capacity for each approach is 1511 pcu/hour, 1961 pcu/hour, and 1767 pcu/hour, with saturation degrees (DS) of 0.39, 0.41, 0.31 respectively and an average of 0.37. Delays range from 18–20 seconds per vehicle and all approaches fall into the LOS C category. The intersection is currently operating smoothly, but regular maintenance and long-term planning are required to address future vehicle growth.